ChemInform Abstract: Review of the Synthesis of Acyclic and Cyclic Oxime Ethers. Issue 15 (24th March 2016) - Mirjafary, Zohreh; Abdoli, Morteza; Saeidian, Hamid; Kakanejadifard, Ali; Farnia, S. Morteza F.
Abstract: Review: [257 refs.